ATLANTIC‐CAMTRAPS: a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America. Issue 11 (1st November 2017) - Lima, Fernando; Beca, Gabrielle; Muylaert, Renata L.; Jenkins, Clinton N.; Perilli, Miriam L. L.; Paschoal, Ana Maria O.; Massara, Rodrigo L.; Paglia, Adriano P.; Chiarello, Adriano G.; Graipel, Maurício E.; Cherem, Jorge J.; Regolin, André L.; et al.
Abstract: Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53, 438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris, crab‐eating fox Cerdocyon thous, tayra Eira barbara, south American coati Nasua nasua, crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.